The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7759/cureus.7456
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-induced Multiple Non-proximal Coronary Spasm in a Patient Presenting with Myocardial Infarction

Abstract: Interventional cardiologists encounter a wide range of lesions that cannot be angiographically distinguished from fixed atherosclerotic obstructive disease. In this case report, we document vasospasm at multiple sites in the coronary territory in a patient presenting with acute coronary syndrome. A 61-year-old woman was referred to our hospital with typical chest pain lasting approximately 1 h. After performing the left coronary artery angiography, a severe tubular stenosis was detected in circumflex (Cx) arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Several case reports in the literature address the benefit of the administration of intracoronary nitroglycerine in patients who presented with ACS, and this action deferred them from PCI [ 22 25 ]. In a case series study by Vishnevsky et al [ 14 ], intracoronary nitroglycerine administration during angiography prior to a scheduled PCI resulted in the resolution of stenosis in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports in the literature address the benefit of the administration of intracoronary nitroglycerine in patients who presented with ACS, and this action deferred them from PCI [ 22 25 ]. In a case series study by Vishnevsky et al [ 14 ], intracoronary nitroglycerine administration during angiography prior to a scheduled PCI resulted in the resolution of stenosis in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Esenboga et al reported that in patients presenting with myocardial infarction (MI) catheter-induced multiple nonproximal coronary spasms. 4 Usually, atherosclerotic plaques develop at angulation and bifurcations due to shear stress; hence, ostial LMCA lesions are less frequent than mid and distal LM lesions. 5 If some irregularity is seen in the lesion, then atherosclerotic lesions may be more likely.…”
Section: Discussionmentioning
confidence: 99%